Metaphors, domains and embodiment - Botha, M. E. (Koers, 2005)
Investigations of metaphorical meaning constitution and meaning (in-) variance have revealed the significance of semantic and semiotic domains and the contexts within which they function as basis for the grounding of metaphorical meaning. In this article some of the current views concerning the grounding of metaphorical meaning in experience and embodiment are explored. My provisional agreement with Lakoff, Johnson and others about the “conceptual” nature of metaphor rests on an important caveat, viz. that this bodily based conceptual structure which lies at the basis of linguistic articulations of metaphor, is grounded in a deeper ontic structure of the world and of human experience. It is the “metaphorical” (actually “analogical”) ontological structure of this grounding that is of interest for the line of argumentation followed in this article. Because Johnson, Lakoff and other’s proposal to ground metaphorical meaning in embodiment and neural processes is open to being construed as subjectivist and materialist, I shall attempt to articulate the contours of an alternative theory of conceptual metaphor, meaning and embodiment which counteracts these possibilities. This theory grounds metaphorical meaning and meaning change in an ontological and anthropological framework which recognises the presence and conditioning functioning of radially ordered structures for reality. These categorisations in which humankind, human knowledge and reality participate, condition and constrain (ground) analogical and metaphorical meaning transfer, cross-domain mappings, and blends in cognition and in language, provide the basis for the analogical concepts found in these disciplines.